Teachers' Attitudes Towards Inclusive Education: A Literature Review - Dede Supriyanto (The Center for Disability Studies and Services Brawijaya University, 2019)
This study conducted to investigate the teachers' attitudes towards inclusive education, and what variables are influenced to their attitudes. A review of 27 literatures that involves 5471 teachers resulted that most of the teacher hold positive attitudes towards inclusive education. Some studies also report negative and neutral attitudes. The term of attitudes was defined differently among the studies. The variables that found influence to the attitudes include are found on teacher's educational degree and background, teacher training, and the type of the disability. The implication of the attitudes towards inclusion were discussed.